Estimation of genetic parameters for four Peruvian guinea pig lines - Cedano-Castro, José Isaí (2021)
CONCYTEC co-funded this research through its project execution unit FONDECYT, as part of the project: 178-2015-FONDECYT - Doctorado en Ciencia Animal.